In vivo analgesic and anti-inflammatory activities of Rosmarinus officinalis aqueous extracts, rosmarinic acid and its acetyl ester derivative. (September 2013) - Lucarini, Rodrigo; Bernardes, Wagner A.; Ferreira, Daniele S.; Tozatti, Marcos G.; Furtado, Ricardo; Bastos, Jairo K.; Pauletti, Patrícia M.; Januário, Ana H.; Silva, Márcio L. Andrade e; Cunha, Wilson R.
Abstract Context: Despite several pharmacological applications of Rosmarinus officinalis L. (Lamiaceae), studies on its analgesic and anti-inflammatory properties have been scarce. Objective: The aim of this work was to use in vivo models to evaluate the analgesic and anti-inflammatory activities of the aqueous extracts obtained from leaves (AEL) and stems (AES) of Rosmarinus officinalis, as well as its isolated compound – rosmarinic acid (RA). We also prepared and assessed the acetyl ester derivative of RA. Materials and methods: The analgesic activity was evaluated using abdominal constriction and formalin tests. For the evaluation of the anti-inflammatory effects, carrageenin-induced paw edema in rats were used. The extracts were used at doses of 100, 200 and 400 mg kg−1 compounds were tested at 10, 20 and 40 mg kg−1. Results: Orally administered AEL, AES and RA were not significantly active at any of the doses tested during the abdominal constriction test; the acetyl ester derivative of RA displayed significant analgesic activity. In the carrageenin-induced paw edema assay, the acetyl derivative of RA at all the tested doses produced significant anti-inflammatory effects and reduced the number of paw licks in the second phase of the formalin test. Discussion and conclusion: The results suggest that the analgesic effects of the acetyl derivative of RA operate via a peripheral-mediated mechanism. The acetyl ester derivative of RA is potentially applicable as a new lead compound for the management of pain and inflammation.